Exponent and Scrambling Index of Some Composite Graphs - Linna Syahputri; Saib Suwilo; Mardiningsih Mardiningsih (ZERO: Jurnal Sains, Matematika dan Terapan, 2026)
A connected graphs G is primitive provided there is a positive integer k such that for each pair of vertices u and v in G there exists a uv-walk of length k. The scrambling index of a primitive graph G, , is the smallest positive integer k such that for each two vertices u and v there is a vertex w with the property that there exist a uw-walk and a vw-walk of length k. We discuss the scrambling index of the joint and the corona product of two vertex disjoint graphs. For such graphs, we discuss their primtivity and then we present their scrambling index.